The Effects of Steaming on Color and Carotenoid Absorption Spectra of Orange-, Yellow- and Purple-Fleshed Sweet Potatoes (Ipomoea batatas (L.) Lamb.) - Soegiarto, Maria Ika Putri; Heriyanto, Heriyanto; Adhiwibawa, Marcelinus A.S.; Widyastuti, Endrika; Putri, Widya Dwi Rukmi; Limantara, Leenawaty (Indonesian Journal of Natural Pigments, 2019)
Sweet potatoes, especially the orange and yellow-fleshed, are functional local food because they contain carotenoids which serve as a pro-vitamin A. The processing of sweet potatoes into noodles, fermented cassava or â€œtapeâ€ and artificial rice is usually prepared through steaming. However, carotenoid is susceptible to degrade when it is subjected to high temperature, such as steaming. The objective of this research is to determine the effects of steaming on the color and carotenoid absorption spectra of local and excellent sweet potatoes which are correlated to the carotenoid content and to evaluate the difference of carotenoid spectral properties among sweet potatoes by principal component analysis (PCA). The steaming treatment decreased color values, such as lightness, redness, and yellowness. In addition, this process also influenced the spectral properties of carotenoid extracts of sweet potatoes. Steaming decreased absorbance and resulted in hypsochromic and bathochromic shifts. Madu Mojokerto, Manohara, local purple fleshed, Beta 1, and Papua Solossa sweet potatoes experienced some decreases in absorbance and a hypsochromic shift of Â± 77 % and Â± 2 nm, Â± 40 % and Â± 21 nm, Â± 63 % and Â± 28 nm, Â± 44 % and Â± 2 nm, and Â± 20 % and Â± 23 nm, respectively; while Antin 3 sweet potatoes experienced some decrease in absorbance of Â± 36 % and a bathochromic shift of Â± 28 nm. The PCA results showed that there were four groups of sweet potatoes based on spectrum shape and absorbance value.